Acute toxicity of dichlorvos (DDVP) to fingerling mirror carp, Cyprinus carpio L. - Ural, MS; Çalta, M (Springer, 2005)
[Abstract Not Available]
Keywords: Abramis-Brama L; Pesticides; Bream; Insecticide